BACE1 activity regulates cell surface contactin-2 levels - Gautam, Vivek (BioMed Central, 2014)
BACKGROUND: Although BACE1 is a major therapeutic target for Alzheimer’s disease (AD), potential side effects of BACE1 inhibition are not well characterized. BACE1 cleaves over 60 putative substrates, however the majority of these cleavages have not been characterized. Here we investigated BACE1-mediated cleavage of human contactin-2, a GPI-anchored cell adhesion molecule. RESULTS: Our initial protein sequence analysis showed that contactin-2 harbors a strong putative BACE1 cleavage site close to its GPI membrane linker domain. When we overexpressed BACE1 in CHO cells stably transfected with human contactin-2, we found increased release of soluble contactin-2 in the conditioned media. Conversely, pharmacological inhibition of BACE1 in CHO cells expressing human contactin-2 and mouse primary neurons decreased soluble contactin-2 secretion. The BACE1 cleavage site mutation 1008MM/AA dramatically impaired soluble contactin-2 release. We then asked whether contactin-2 release induced by BACE1 expression would concomitantly decrease cell surface levels of contactin-2. Using immunofluorescence and surface-biotinylation assays, we showed that BACE1 activity tightly regulates contactin-2 surface levels in CHO cells as well as in mouse primary neurons. Finally, contactin-2 levels were decreased in Alzheimer’s disease brain samples correlating inversely with elevated BACE1 levels in the same samples. CONCLUSION: Our results clearly demonstrate that mouse and human contactin-2 are physiological substrates for BACE1. BACE1-mediated contactin-2 cleavage tightly regulates the surface expression of contactin-2 in neuronal cells. Given the role of contactin-2 in cell adhesion, neurite outgrowth and axon guidance, our data suggest that BACE1 may play an important role in these physiological processes by regulating contactin-2 surface levels.